Long-read microbial genome assembly, gene prediction and functional annotation: a service of the MIRRI ERIC Italian node - Contaldo, Sandro Gepiro; d’Acierno, Antonio; Bosio, Lorenzo; Venice, Francesco; Perottino, Elisa Li; Hoyos Rea, Janneth Estefania; Varese, Giovanna Cristina; Cordero, Francesca; Beccuti, Marco (Frontiers in Bioinformatics, 2025)
BackgroundUnderstanding the structure and function of microbial genomes is crucial for uncovering their ecological roles, evolutionary trajectories, and potential applications in health, biotechnology, agriculture, food production, and environmental science. However, genome reconstruction and annotation remain computationally demanding and technically complex.ResultsWe introduce a bioinformatics platform designed explicitly for long-read microbial sequencing data to address these challenges. Developed as a service of the Italian MIRRI ERIC node, the platform provides a comprehensive solution for analyzing both prokaryotic and eukaryotic genomes, from assembly to functional protein annotation. It integrates state-of-the-art tools (e.g., Canu, Flye, BRAKER3, Prokka, InterProScan) within a reproducible, scalable workflow built on the Common Workflow Language and accelerated through high-performance computing infrastructure. A user-friendly web interface ensures accessibility, even for non-specialists.ConclusionThrough case studies involving three environmentally and clinically significant microorganisms, we demonstrate the ability of the platform to produce reliable, biologically meaningful insights, positioning it as a valuable tool for routine genome analysis and advanced microbial research.